(untitled) (Bangladesh Journal of Medical Science, 2023)
Twenty –five isolates of Escherichia coli isolated from cases of diarrhea in children under five years of age were obtained, characterized by Extensively Drug-Resistant(XDR) resistance patterns, and sensitivity screening of isolates was performed.E7 isolates were resistant to 4 groups of antibiotics and E5 - E13 - E14 - E17 - E18 - E20 - E47 - E46 - E42 - E31 - E26 isolates resistant to 5 groups of antibiotics and 48E isolate resistance to 6 groups of antibiotics and consisting of E2 E38 - E36 - E34 - E28 - E16 - E10isolates showed resistance to 7 groups of antibiotics, and E41 - E24 - E19 - E9 –E1 isolates resistance to 8 groups of antibiotics. The genotyping of 25 E.coliisolates was carried out by Pulsed-field Gel Electrophoresis (PFGE) using restriction endonucleases (Xbal) which belong to different phylogenetic groups, were as group A, group B2, group D (2/25 and 8%) group C (4/25 and 16%), group F (3/25 and 12%), group E (12/25 and 48%). The genetic convergence rate of isolates is 83%, and this is due to the similarity in genetic content, the source of isolation, and the place of isolation itself. Bangladesh Journal of Medical Science Vol.22 (Special Issue) 2023 p.18-24